2019
DOI: 10.3345/kjp.2018.06863
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and tolerability of adjunctive perampanel treatment in children under 12 years of age with refractory epilepsy

Abstract: Purpose There is limited data on the use of perampanel in children under 12 years of age. We evaluated the efficacy and tolerability of adjunctive perampanel treatment in children under 12 years of age with refractory epilepsy. Methods This retrospective observational study was performed in Kyungpook National University Hospital from July 2016 to March 2018. A responder was defined as a patient with ≥50% reduction in monthly seizure frequency compared with the baseline.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 15 publications
3
20
0
Order By: Relevance
“…The results were compatible with previous studies in children over 12 years. According to previous studies, the responder rates were 31%-68% in children with refractory epilepsy under 18 years, whereas the rate of seizure freedom ranged from 9 % to 23 % [7,10,11]. Therefore, the efficacy of PER as adjunctive therapy for young children with intractable epilepsy was good.…”
Section: Discussionmentioning
confidence: 98%
“…The results were compatible with previous studies in children over 12 years. According to previous studies, the responder rates were 31%-68% in children with refractory epilepsy under 18 years, whereas the rate of seizure freedom ranged from 9 % to 23 % [7,10,11]. Therefore, the efficacy of PER as adjunctive therapy for young children with intractable epilepsy was good.…”
Section: Discussionmentioning
confidence: 98%
“…PER is a novel antiepileptic drug that selectively inhibits the postsynaptic AMPA receptor and is effective for treating drug-resistant epilepsy. [21][22][23][24][25][26] PER efficacy has been demonstrated in focal epilepsy and, more recently, in primary generalized tonic-clonic seizures. 23,24 A recent open-label study indicated that PER treatment was effective in adults with Lennox-Gastaut syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…26 Recently, two studies reported the efficacy of PER for treating refractory epilepsy complications in various neurodevelopmental disorders. 21,22 However, the previous two reports did not report genotypic data for RTT-P, such as mutations of MECP2, FOXG1, and CDKL5.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yun et al [6] investigated the efficacy and tolerability of adjunctive PER treatment in children under 12 years of age with refractory epilepsy. A total 22 patients, aged 3.1–11.4 years showed responder rate of 68% (≥50% seizure reduction), wherein 23% showed seizure freedom.…”
mentioning
confidence: 99%